Riparian buffers: Disrupting the transport of E. coli from rural catchments to streams. (15th August 2022) - Lim, Timothy J.Y.; Sargent, Robert; Henry, Rebekah; Fletcher, Tim D.; Coleman, Rhys A.; McCarthy, David T.; Lintern, Anna
Highlights: Agricultural and residential catchments have similar E. coli concentrations. Riparian buffers can reduce E. coli concentrations in both dry and wet weather. Riparian buffers coverage correlates with lower E. coli concentrations. Riparian buffers appear to affect concentration-discharge relationships. Abstract: High levels of E. coli and associated faecal microbes in waterways as a result of agricultural and residential land use can pose environmental, human health, and economic risks. This study aims to understand the impacts of land use, climatic variables, and riparian buffers on in-stream E. coli concentrations. Flow, temperature, and E. coli were monitored during three sampling campaigns within eleven independent catchments. These catchments have varying land use and extents of riparian buffer coverage. Results showed that catchments with predominantly agricultural and residential land uses (average = 349.7 MPN/100 mL) had higher E. coli concentrations than predominantly forested catchments (average = 111.8 MPN/100 mL). However, there were no statistically significant differences in E. coli concentrations between the agricultural and residential land uses. Riparian buffers appear to reduce E. coli concentrations in streams, as indicated by significant negative correlations between in-stream E. coli concentrations with the riparian buffer areal coverage (Pearson's r = -0.95, Spearman's ρ = -0.90) and the ratio of buffer length to stream length (Pearson's r = -0.87, Spearman's ρ = -0.90). We find that riparian buffers potentially disrupt transport pathways that govern E. coli movement, which in-turn can affect the concentration-discharge relationship. This reinforces the importance of protecting and restoring riparian buffers along drainage lines in agricultural and rural-residential catchments to improve downstream microbial water quality. Graphical Abstract: Image, graphical abstract